2020
DOI: 10.1097/01.ogx.0000658028.79421.21
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Office-Based Pessary Care: A Randomized Controlled Trial

Abstract: (Abstracted from Obstet Gynecol 2020;135:100–105) Vaginal pessaries are recommended often as first-line treatment of pelvic organ prolapse and stress urinary incontinence, especially for women who do not desire surgery or who are poor surgical candidates. Several studies have shown that pessaries improve symptoms of prolapse, bowel symptoms, body image perception, and overall quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…Whereas there is no universal timing that is used, studies have reported similar outcomes for 3-and 6-month evaluations for patients managed with continuous pessary wear. 22 In appropriate candidates, vaginal estrogen therapy may be helpful in preventing pessary-related erosions in women with atrophic vaginal tissues.…”
Section: Pessary Usementioning
confidence: 99%
“…Whereas there is no universal timing that is used, studies have reported similar outcomes for 3-and 6-month evaluations for patients managed with continuous pessary wear. 22 In appropriate candidates, vaginal estrogen therapy may be helpful in preventing pessary-related erosions in women with atrophic vaginal tissues.…”
Section: Pessary Usementioning
confidence: 99%
“…We defined adverse outcomes as any of the following: vaginal examination findings of blood, discharge, erosion, or pessary dislodgment, need for pessary holiday, and fistula formation. We defined erosion using a system proposed by Propst et al, 23 rating them from epithelial erythema to epithelial breaks or erosions. To compare patterns observed during the COVID-19 pandemic to those before the pandemic, we recorded these pessary outcomes from the same group of women 1 year prior in order to establish a baseline.…”
Section: Methodsmentioning
confidence: 99%
“…Seven studies provided data on risk of adverse events with long-term pessary use (without removal or cleaning) [17][18][19][20][21][22][23]. Nine additional articles were reviewed that provided information of interest during the pandemic [24][25][26][27][28][29][30][31][32].…”
Section: Pessary Managementmentioning
confidence: 99%
“…& Patients can safely extend the time interval between pessary cleanings to 6 months (and, in some cases, up to 24 months) with minimal risk of adverse events [17][18][19][20][21][22][23]. & Patients capable of pessary removal and reinsertion should be encouraged to self-clean their pessary [27,[31][32][33][34][35].…”
Section: Pessary Managementmentioning
confidence: 99%
See 1 more Smart Citation